2009
DOI: 10.1017/s0007114509991814
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilating dipeptide Trp-His can prevent atherosclerosis in apo E-deficient mice

Abstract: Most of the investigations for an alternative medicinal treatment on atherosclerosis have been focused on natural or dietary compounds including phytochemicals. So far, few studies regarding anti-atherosclerotic small peptides except for tetrapeptide of Lys-Arg-Glu-Ser have been reported. The present study was, thus, to investigate whether dipeptide Trp-His, which is one of vasodilating small peptides, could reduce atherosclerotic lesions in apo E-deficient mice fed a high-fat diet. The animal study involved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…We investigated whether the dipeptide Try-His, a vasodilating small peptide, can reduce atherosclerotic lesions in apoEÀ/À mice fed a high-fat diet. 107) The study involved a 9 weeks of successive administration of Try-His at doses of 0, 10, or 100 mg/kg per day. En face analyses provided direct evidence that the atherosclerotic lesion area was significantly reduced, by 27 and 38%, for Try-His dosed at 10 and 100 mg/kg per day respectively, as compared with the control group.…”
Section: Nuclear Hormone Receptorsmentioning
confidence: 99%
“…We investigated whether the dipeptide Try-His, a vasodilating small peptide, can reduce atherosclerotic lesions in apoEÀ/À mice fed a high-fat diet. 107) The study involved a 9 weeks of successive administration of Try-His at doses of 0, 10, or 100 mg/kg per day. En face analyses provided direct evidence that the atherosclerotic lesion area was significantly reduced, by 27 and 38%, for Try-His dosed at 10 and 100 mg/kg per day respectively, as compared with the control group.…”
Section: Nuclear Hormone Receptorsmentioning
confidence: 99%
“…It has also been demonstrated that Trp-His could ameliorate the atherosclerotic vascular dysfunction in apolipoprotein E-deficient mice. 4) However, 1-or 3-methyl-His-Arg-Trp and His-Arg-Ala diminished the power of their mother peptide, His-Arg-Trp, 2) raising speculation that the imidazolium and/or indole moieties from peptides having nitrogen heterocycles may be of importance for relaxing the contracted aorta. In order to gain further insight about the effect of vasoactive peptides on the structural requirements of relaxation, we investigated in this study the relaxation behavior of adenine (6-amino-6H-purine) and its analogues on the contracted aorta, since adenine has structural similarity with the side-chains of Trp-His.…”
mentioning
confidence: 99%
“…Therefore, we currently investigate a role of GGC as a cell-penetrating pepide by assessing its cellular uptake using an animal model. Administration of dipeptides influence atherosclerotic development in apo E-deficient mouse models (Matsui et al 2010) and immune responses and mRNA expression of GCS-HS in both humans and mice with compromised immune functions (Murakami et al 2009;Takagi et al 2010). Oligopeptides inhibit TNFα-induced activation of NF-κB in human aortic endothelial cells (Ringseis et al 2009) and ROS formation by inducing the expression of antioxidant enzymes, superoxide dismutase (SOD) and heme oxygenase, in mice (White et al 2009).…”
Section: Discussionmentioning
confidence: 99%